2015
DOI: 10.3109/17435390.2014.993344
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure to carbon nanotube-based aerosols does not affect the functional properties of a 3D human epithelial airway model

Abstract: -Rutishauser (2015) Repeated exposure to carbon nanotube-based aerosols does not affect the functional properties of a 3D human epithelial airway model, Nanotoxicology, 9:8, 983-993, DOI: 10.3109/17435390.2014 2 ) were applied to the co-culture system, either over one day (one day repeated exposure) or three days (three day repeated exposure scenario). Although in both repeated exposure scenarios MWCNTs were found to interact with the different cell types, they did not induce any cytotoxicity or alterations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 65 publications
2
59
0
Order By: Relevance
“…29 MWCNTs were thoroughly characterized prior to and after the aerosolization process, as described in previous work. 25,27,30 The size distributions of the stock and deposited MWCNTs, as well as all other key physicochemical characteristics of the MWCNT Figure 1. Schematic presentation of the exposure scenario.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 MWCNTs were thoroughly characterized prior to and after the aerosolization process, as described in previous work. 25,27,30 The size distributions of the stock and deposited MWCNTs, as well as all other key physicochemical characteristics of the MWCNT Figure 1. Schematic presentation of the exposure scenario.…”
Section: Resultsmentioning
confidence: 99%
“…The ALICE system is a well-established aerosolization system for spherical NPs 21,24 and was recently demonstrated to be efficient for the aerosolization of fiber-shaped nanomaterials, such as cellulose nanocrystals and MWCNTs for single and short-term repeated exposures. 25,26 For the current study a stable, well-characterized, and well-dispersed MWCNT 27 suspension was aerosolized using the ALICE system. For the current work Pluronic F127 has been used as a dispersant since it prevents MWCNT aggregation during the experimental work procedure and results in a well-dispersed suspension, allowing an efficient aerosolization.…”
Section: Resultsmentioning
confidence: 99%
“…The ALICE is a well-established system that delivers aerosols in a dosecontrolled manner. It has been used to study the potentially hazardous effects of different types of nanomaterials 23,47 and AuNPs. 48 After nebulization of the AuNP suspensions onto the lung cell surface, cocultures were post-incubated for 24 h. 47 dH 2 O containing 0.9% NaCl was used as control, with a QCM deposition value of 0 μg/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In order to visualize the AuNPs after the nebulization process, TEM grids were integrated inside the exposure chamber and, after exposure, were left to dry in order to visually confirm uniform deposition of the AuNPs. Coculture samples were prepared as described by Chortarea et al 47 Briefly, after the exposure and 24 h incubation, inserts were fixed with 2.5% glutaraldehyde in HEPES buffer, then postfixed with 1% osmium tetroxide. This was followed by dehydration via graded ethanol series as well as Epon embedding.…”
Section: Methodsmentioning
confidence: 99%
“…15 Furthermore, in a study conducted with nebulized MWCNTs, it was shown that after 24 h postexposure of a single dose (0.14−0.39 μg/cm 2 ), MWCNT were mainly found in macrophages of the same coculture model that was employed in the present study. 65 It is noted that while longerterm effects of materials retained in the lung would be important to study, the cell model employed here is limited to be used over a period of 3 days; therefore further studies would be necessary to be performed in vivo.…”
Section: 36mentioning
confidence: 99%